Studi Pola Operasi Normal Waduk Mamak di Kabupaten Sumbawa Provinsi Nusa Tenggara Barat - Kurnianto, Noval Irfan; Wahyuni, Sri; Sholichin, Moh. (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
The reservoir operation of Mamak reservoir in Sumbawa Regency Province of West Nusa Tenggara with trial and error method and it’s also not equipped with Rule Curve for Reservoir Operation so It’s faced with limited water availability in water releasing for dry season.The purpose of this study was to analyze about potential inflow and the irrigation water requirement based on planting pattern scenario. From the analysis that has been done is expected to provide an overview about the rule curve of normal operation. By  ± 81,87 million m3 of potential inflow in wet season and ± 41,14 million  m3 in dry season, the lowest irrigation water requirement was found on MT – I December-1, in wet season need to apply K factor = 0,70 for MT-I and K factor = 0,60 for MT-II to reduce that number of irrigation water requirement by ±38,73 million m3.In analyzing irrigation water requirement, It also planned with three period of planting pattern scenario so the amount of irrigation water requirement equals to 61,23 million m3 in wet season, and in dry season need to apply K factor = 0,70 for MT-I and K factor = 0,60 for MT-II. Operator can set water level on normal operation area based on the rule curve of normal operation.